The Thin Line of Relationship Between Intimate Partner Violence and Depression: La delgada línea de relación entre la violencia de pareja y la depresión | 亲密伴侣暴力与抑郁症之间微妙的关系 - Pinedo Linasca, Romina (2024)
Intimate partner violence and depression are serious and widespread problems worldwide. According to an analysis of prevalence data in 161 countries from 2000 to 2018 by the WHO, one in three women has suffered physical and/or sexual violence by their partner or sexual violence by someone who was not their partner, or both. In the Western Pacific, the prevalence is 20% and 22% in the European Region and high-income countries (1). In our country, according to the results of Endes 2018, 63.2% of women aged 15 to 49 years were victims of domestic violence at some point in their lives by their husband or partner. According to the type of violence exerted, 30.7% of the victims suffered physical violence, 58.9% psychological or verbal violence, and 6.8% sexual violence.